Association between thyroid hormone sensitivity and ischemic stroke-associated pneumonia: The role of FT3/FT4 ratio - Zhidan Hua; Zichen Rao; Yiming Zhang; Chunyan Zhu (PLoS ONE, 2025)
Background Thyroid hormone sensitivity has emerged as a critical factor in various diseases. However, its relationship with ischemic stroke-associated pneumonia (iSAP) in euthyroid patients with ischemic stroke remains poorly understood. This study aims to elucidate the association between thyroid hormone sensitivity indices and iSAP risk. Methods A total of 1,767 euthyroid patients with ischemic stroke were enrolled and categorized into the iSAP group (n = 376) and the non-iSAP group (n = 1,391). Univariate and multivariate logistic regression analyses were performed to assess the association between thyroid hormone sensitivity indices-including free triiodothyronine (FT3), free thyroxine (FT4), FT3/FT4 ratio, thyroid-stimulating hormone index (TSHI), Thyrotroph T4 Resistance Index (TT4RI), and thyroid feedback quantile-based indices (TFQI-FT3, TFQI-FT4)-and iSAP risk. The predictive performance of these indices was evaluated using receiver operating characteristic (ROC) curve analysis. Results Compared with the non-iSAP group, patients with iSAP were older and exhibited a higher prevalence of atrial fibrillation (AF) and chronic obstructive pulmonary disease (COPD), along with greater stroke severity (higher NIHSS scores). Univariate analysis demonstrated that higher FT3 levels (OR = 0.85, 95% CI: 0.80–0.91, p < 0.0001) and a higher FT3/FT4 ratio (OR = 0.80, 95% CI: 0.69–0.92, p = 0.0018) were statistically associated with lower odds of developing iSAP. After adjusting for confounders, multivariate analysis revealed that a higher FT3/FT4 ratio remained inversely associated with iSAP occurrence (Q3 vs. Q1: OR = 0.40, 95% CI: 0.26–0.62, p < 0.0001; Q4 vs. Q1: OR = 0.31, 95% CI: 0.19–0.48, p < 0.0001). Additionally, elevated TFQI-FT3 levels showed a significant inverse association with iSAP occurrence (OR = 0.35, 95% CI: 0.18–0.67, p = 0.0017). ROC analysis demonstrated that the FT3/FT4 ratio and the Age, Atrial fibrillation, Dysphagia, Sex, and Stroke Severity(A2DS2)score exhibited moderate predictive accuracy for iSAP, with area under the curve (AUC) values of 0.711 and 0.763, respectively. Conclusion In euthyroid patients with ischemic stroke, a lower FT3/FT4 ratio and reduced TFQI-FT3 levels were linked to higher odds of iSAP. These exploratory findings suggest that thyroid hormone sensitivity indices, particularly the FT3/FT4 ratio, may serve as potential predictive markers and warrant validation in prospective studies.